Radiation effects on MHD flow and heat transfer over a stretching sheet with convective boundary conditions - Norhafizah, Md Sarif; Mohd Zuki, Salleh; Roslinda, Nazar; Razman, Mat Tahar (AIP Publishing LLC., 2013)
In this study, the steady magnetohydrodynamic (MHD) boundary layer flow over a stretching sheet with radiation effect under convective boundary conditions, where the heat is supplied to the convecting fluid through a bounding surface with a finite heat capacity, is considered. The governing system of partial differential equations is transformed into ordinary differential equations, which are then solved numerically via the Keller-box method. The effects of the governing parameters on the flow and heat transfer characteristics are analyzed and discussed. It is found that as the Prandtl number Pr and the radiation parameter increase, the temperature profile decreases, while as the magnetic and convective parameters decrease, the temperature profile also decreases.